PENGARUH PROGRAM CETAK 1 JUTA HA SAWAH BARU TERHADAP PRODUKSI PADI DAN KESEJAHTERAAN PETANI - Dahiri (Pusat Kajian Anggaran, 2018)
Data on the area of national rice fields and rice production showed an increasing trend, but the welfare of farmers also declined. The purpose of this research is first to calculate the impact of rice field area and productivity to rice production, secondly calculate the influence of wetland area, productivity, and price to farmer's welfare, thirdly count the effectiveness of paddy production and the program of 1 million ha of new fields. The method used is regression with natural logatirma and data of 33 provinces in Indonesia year 2013-2016. The result of data analysis showed that first wetland area and productivity have positive and significant effect to production, both wetland area, productivity, and price have positive effect to farmer welfare but only significant land area, three effectiveness of paddy production in quite effective category and program effectiveness print 1 million ha of new fields in the category of ineffective.